2020
DOI: 10.1038/s41588-020-0646-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent inversion toggling and great ape genome evolution

Abstract: Inversions play an important role in disease and evolution but are difficult to characterize because their breakpoints map to large repeats. We increased by six-fold the number ( n = 1,069) of previously reported great ape inversions using Strand-seq and long-read sequencing. We find that the X chromosome is most enriched (2.5-fold) for inversions based on its size and duplication content. There is an excess of differentially expressed primate genes near the breakpoints of large (>100 kb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 73 publications
(142 reference statements)
6
67
1
Order By: Relevance
“…Conversely, 327 regions (87%), ranging in size from 859 bp to 9 Mbp and amounting to 55.6 Mbp of inverted DNA, were novel and described here for the first time as human/macaque inversions. However, 58 of these 327 regions were previously found to be inverted in Hominidae in a study in which Strand-seq was applied to discover inversions between humans and great apes (Porubsky et al 2020b), and 11 out 327 have been described to be polymorphic inversions in human (Antonacci et al 2009;Chaisson et al 2019;Giner-Delgado et al 2019;Puig et al 2020).…”
Section: Comparison Of Human and Macaque Assemblies And Published Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, 327 regions (87%), ranging in size from 859 bp to 9 Mbp and amounting to 55.6 Mbp of inverted DNA, were novel and described here for the first time as human/macaque inversions. However, 58 of these 327 regions were previously found to be inverted in Hominidae in a study in which Strand-seq was applied to discover inversions between humans and great apes (Porubsky et al 2020b), and 11 out 327 have been described to be polymorphic inversions in human (Antonacci et al 2009;Chaisson et al 2019;Giner-Delgado et al 2019;Puig et al 2020).…”
Section: Comparison Of Human and Macaque Assemblies And Published Literaturementioning
confidence: 99%
“…To gather more information regarding the lineage specificity of the inversions, we used inversion calls generated for great apes, also from Strand-seq data (Porubsky et al 2020b), and net alignments for the most recent releases of genome assemblies of two New World monkey outgroup species (C. jacchus, calJac3; Saimiri boliviensis, saiBol1). This revealed that 49.1% (184/375) of the inversions occurred in the Old World monkeys, whereas 43.5% (163/375) are specific to Hominidae.…”
Section: Evolutionary Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, we also ran our assembly pipeline on the HiFi datasets of the two parents, yielding assemblies that were slightly less continuous due to the lower input coverage (contig N50: HG00731: H1, 19.9 Mbp; H2, 20.1 Mbp; HG00732: H1, 10.4 Mbp; H2, 10.8 Mbp) (Supplementary Table 1). To verify the ability to also process nonhuman data 31 , we clustered squashed contigs from a gorilla PacBio assembly and correctly assigned contigs to 24 clusters while, at same time, resolving known reciprocal translocations between chromosomes 5 and 17 (in humans) ( Supplementary Fig. 8).…”
mentioning
confidence: 99%
“…Our SHIMS 3.0 assemblies each derive from a single male individual, but in light of the results from Small and colleagues, who found that human P24 spacers are inverted in 18% of European X Chromosomes, we would anticipate that inversion polymorphisms exist within all three species. Indeed, a recent study found that 10 out of 13 newly identified X chromosome inversion polymorphisms in chimpanzee and/or bonobo occurred in X palindromes (Porubsky et al 2020).…”
Section: Structural Changes Between Species Are Concentrated Around the Center Of Symmetrymentioning
confidence: 99%